Homo Sum $1 (BVolume 04s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"Homo Sum $1 (BVolume 04" by Georg Ebers is a historical novel likely written in the late 19th century. This volume continues the deeply personal and dramatic narrative involving themes of love, art, and moral struggles set against the backdrop of early Christian society clashing with pagan cultures. The story$1 (Bs focus is on the character Polykarp, a gifted sculptor, who grapples with his feelings for Sirona, the wife of another man, leading to conflicts that resonate with issues of purity, faith, and the pursuit of artistic integrity. This installment of "Homo Sum" showcases Polykarp's artistic endeavors and emotional turmoil as he creates a bust of Sirona, reflecting his unfulfilled love for her. He is caught in a fierce internal struggle between his creative passion and societal moral codes as his mother confronts him about his intentions. Meanwhile, Sirona, who has fled from her abusive husband Phoebicius, also finds her life entwined with Polykarp's feelings, evoking themes of innocence and redemption. The novel adeptly develops the tension between personal desires and societal expectations, culminating in poignant scenes that explore both characters' hopes and the complications that arise from their intertwined fates. The dynamics of family, art, and love highlight the struggles of the individuals within the complex societal norms of their time. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: German fiction -- Translations into English; Church history -- 4th century -- Fiction